SEHATI: Development of an Educational Board Game for Interactive Sexual Education of Individuals with Hearing Impairments - I Putu Aprika Apsarendra Putra; Ni Kadek Septiari; Putu Aditya Antara (Bisma The Journal of Counseling, 2025)
The lack of interactive and accessible learning media remains a major challenge in delivering sexual education to individuals with hearing impairments. This condition potentially leads to limited understanding of reproductive health and safe sexual behavior among this group. This study aimed to analyze and evaluate the effectiveness of developing the SEHATI educational board game as a learning medium to enhance sexual education understanding among individuals with hearing impairments. This research employed a research and development (R&D) approach using an instructional media development design. The research subjects consisted of two media experts, two subject-matter experts, and ten students with hearing impairments involved in a limited trial. Data were collected through observations, interviews, and feasibility questionnaires, using expert validation sheets and user response questionnaires as research instruments. Data were analyzed using quantitative and qualitative descriptive analysis to determine the feasibility of the developed media and students’ responses to the educational board game. The results show that the SEHATI educational board game is highly feasible based on expert evaluation and received positive responses from students. The media enhances learning engagement and understanding of sexual education concepts among individuals with hearing impairments. Overall, SEHATI serves as an innovative and inclusive learning medium for reproductive health education.